De l’analyse de la médiation aux recherches sur la réception par les publics : quarante ans d’exploration à l’École du Louvre - Marie-Clarté O’Neill (Les Cahiers de l'École du Louvre)
This article provides an historical overview of the consideration given to the study of audiences in curricula and, above all, in the research work carried out by Master 1 and 2 students at the École du Louvre, from the 1990s to the 2020s. An analysis of this chronology highlights both a part of the history of museology and museums, and the gradual shift from a description and analysis of mediation to the beginnings of applied research into the scientific reception of exhibitions by visitors. Based on the principles of constructivist education, i.e., the study of the relationship between the intellectual functioning of visitors and the various aspects of museography, the research presented provides the beginnings of what should enable us to better grasp the components of a visitor experience, often evoked by museology, but too little precisely described.